Cobalt-catalyzed directed C–H alkenylation of pivalophenone N–H imine with alkenyl phosphates - Xu, Wengang (2018)
A cobalt–N-heterocyclic carbene (NHC) catalyst efficiently promotes an ortho C–H alkenylation reaction of pivalophenone N–H imine with an alkenyl phosphate. The reaction tolerates various substituted pivalophenone N–H imines as well as cyclic and acyclic alkenyl phosphates.